A view from the top: how South African women leaders shatter the glass ceiling - Mathetha, Kholosa; Dhanpat, Nelesh (Frontiers in Sociology, 2025)
This study investigates how South African women leaders navigated the glass ceiling to reach senior leadership positions. We explored the barriers these leaders encountered and examined the strategies they used to overcome workplace obstacles. We conducted semi-structured interviews with 15 women holding senior leadership positions across various South African industries. We selected participants through purposive and snowball sampling and analyzed data through Interpretative Phenomenological Analysis (IPA) to identify recurring patterns and themes. The analysis revealed four critical themes. First, participants faced persistent organizational barriers, including inadequate career support mechanisms and institutional bias in promotion decisions. Second, successful advancement required three core strategies: mentorship, strategic networking, and continuous skills development. Third, participants developed leadership presence through what they termed “positive influential femininity,” with many women actively practicing female empowerment within their organizations. Fourth, work-life integration presented ongoing challenges, requiring robust support systems and flexible organizational policies. Despite reaching senior positions, participants encountered continuing barriers. Women reported hitting additional glass ceiling effects at C-suite level, whilst most faced persistent gender stereotypes that limited their progression to executive roles. However, many participants successfully mentored other women into leadership positions, creating advancement pathways for future female leaders. These findings provide evidence-based strategies for dismantling glass ceiling barriers and offer practical approaches for organizations seeking to accelerate women's leadership advancement in South Africa's evolving corporate landscape.